Internalisasi Nilai-Nilai Kewirausahaan Etnis Madura - Adi, Khofifatu Rohmah; Idris, Idris; Rosyida, Fatiya (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Madurese is an ethnic group that we encounter in many cities. This ethnicity is usually attached to the image of the merchant. Besides this image, Madura also attaches to the image of newcomers. How this ethnic group became very attached to the merchant's identity indeed cannot be separated from the role of parents. The family environment is very instrumental in directing or learning children. The purpose of this research is to find out how to internalize these ethnic entrepreneurial values—this research designed using a qualitative approach. Data collection techniques are done through observation and in-depth interviews. Interview techniques are used to reveal how to internalize the value of entrepreneurship towards families, especially children. The research findings show that in some ethnic Madurese, there is no internalization process of entrepreneurial values in their families, but in other parts, this process occurs. Furthermore, the findings in the field show that the experience of parents influences the internalization process. The process of internalizing entrepreneurial values did by modeling or giving examples by parents, involvement, and habituation of parents' activities to children. Involvement did and verbally begins by inviting children to help with the work of parents. Most entrepreneurs tend to learn from the experience of joining parents or family. The values adopted by children in this ethnicity are self-confidence, high work ethic.DOI: 10.17977/um022v5i12020p001